Real - time temperature monitoring system using MATLAB - Nur Liyana, Yusoff (2012)
This project involves the implement of temperature sensor for industrial related applications in real-time. The purpose of this project is to monitor and measure the temperature level of liquid or water. This project not only involves the development of the Matlab software for monitoring purpose but also includes the development of the sensor system. The sensor that will be use is the temperature sensor which can measure the temperature of liquid or water and with suitable temperature range. The sensor system should have DAQ capabilities using DAQ cards which available in the laboratory. Matlab Programming language will be use to develop interface for the sensor system. GUI (Graphical User Interface) is consists of buttons that user easily can view the temperature will be creating using Matlab software which is to monitor the temperature. The value of the temperature will be detecting automatically base on the system and transfer the value using serial USB port to the computer. Matlab will collect and record the data in graph format. In this system, the developed sensor should capable to measure temperature in real-time. The system also should capable to store and retrieve data for further analysis. The sensor system will be tested in the laboratory environment and/or in real industrial applications.